Parents and coach support towards swimming athletic achievement - Dewa Gede Anom Artha Tanaya; Suratmin Suratmin; Luh Putu Tuti Ariani (Altius: Jurnal Ilmu Olahraga dan Kesehatan, 2023)
Motivation contributes a big influence on the progress of swimming athlete achievement. One of them is extrinsic motivation which becomes encouragement from outside the individual such as the support of parents, coaches, friends, and the surrounding environment. The study aimed to determine the parent's and coaches' support for the achievements of swimming athletes in the Denpasar club. The research was conducted through a qualitative descriptive approach with a survey method. The sample was 80 parents and 5 coaches with a population of 155 people at a swimming club in Denpasar. The data were carried out through observation, questionnaires, interviews, and documents. The data were analyzed by descriptive statistical analysis method. The results showed that: (1) the parental support for swimming athlete achievement was 30% (very supportive), 52% (supportive), 18% (less supportive), and (2) coach support for swimming athlete achievement was 80 % (strongly supports), 0% (supports), and 20% (fewer supports). It simply stated that parental support in achieving achievement is supportive, while the coach's support in achieving achievement is very supportive of the swimming club in Denpasar. It is suggested that the involvement of parents and coaches is important in coaching and achieving achievements.